2015
DOI: 10.1039/c5ra15173b
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical approach to understand the inhibition mechanism of steel corrosion with two aminobenzonitrile inhibitors

Abstract: ARTICLEThis journal is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(41 citation statements)
references
References 63 publications
2
39
0
Order By: Relevance
“…The dynamic simulation was carried out by this force eld. 36,37,39 In this particular investigation, MD simulations were performed with NVT canonical ensemble for a simulation time of 100 ps with 1.0 fs time step at 298 K. The interaction energy (E interaction ) between the iron surface and the inhibitor molecules is described as the difference between the total energy and the sum of energy of iron surface together with H 2 O, H 3 O + , Cl À along with the single point energy of the inhibitor molecule. 36 The negative of the interaction energy presents the binding energy of the inhibitor molecules as follows: 36,37,39 E binding ¼ ÀE interaction 73.…”
Section: Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic simulation was carried out by this force eld. 36,37,39 In this particular investigation, MD simulations were performed with NVT canonical ensemble for a simulation time of 100 ps with 1.0 fs time step at 298 K. The interaction energy (E interaction ) between the iron surface and the inhibitor molecules is described as the difference between the total energy and the sum of energy of iron surface together with H 2 O, H 3 O + , Cl À along with the single point energy of the inhibitor molecule. 36 The negative of the interaction energy presents the binding energy of the inhibitor molecules as follows: 36,37,39 E binding ¼ ÀE interaction 73.…”
Section: Computational Studiesmentioning
confidence: 99%
“…The high negative interaction energy values are attributable to strong adsorption of the molecules on the Fe surface. 37,39 Valuable information regarding the adsorption behavior of inhibitors can be extracted from the interaction energy (E interaction ) or binding energy (E binding ) values as shown in Table 6. The results of E interaction indicated that the combination of CS and AMT interacts more strongly than AMT and CS alone with the Fe (1 1 0) surface.…”
Section: Surface Analysismentioning
confidence: 99%
“…The results showed increasing in dipole moment μ and decreasing in electrophilicity ω, electronegativity X, electronic affinity A and ionization energy I, these differences in quantum values between HAT compound and its protonated forms confirmed the suggested interaction between HAT + and metal surface. Also, the inhibition efficiency of the inhibitor is very effected by the energy gap (▵E) that it is related to adsorption ability of the inhibitor on steel surface, the low value of (▵E) leads to increase the reactivity of the inhibitor . It is also noted here that the E HOMO values of neutral HAT inhibitor are higher than those for protonated forms, this means that the HAT (+ ° H2) and HAT (+NH3) forms have the low ability of electron‐donating compared with the HAT.…”
Section: Resultsmentioning
confidence: 73%
“…η Fe and η inh correspond to the hardness of iron and inhibitor. If ΔN > 0, inhibitor to metal electron transfer will occur or vice versa if ΔN < 0 . The positive value of ΔN indicates that both the inhibitors donate electrons to metal vacant d orbital.…”
Section: Resultsmentioning
confidence: 99%
“…If DN > 0, inhibitor to metal electron transfer will occur or vice versa if DN < 0. [46] The positive value of DN indicates that both the inhibitors donate electrons to metal vacant d orbital. As number of electron transferred DN is higher for I 1 than I 2, I 1 has the higher inhibition efficiency.…”
Section: Quantum Chemical Studiesmentioning
confidence: 99%